2008
DOI: 10.1007/s00134-008-1201-x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal continuous positive airway pressure decreases respiratory muscles overload in young infants with severe acute viral bronchiolitis

Abstract: In young infants with severe acute respiratory syncytial virus bronchiolitis, nCPAP rapidly unloads respiratory muscles and improves respiratory distress symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
17

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 31 publications
4
119
0
17
Order By: Relevance
“…Third, acute bronchiolitis leading to PICU admission occurs often in babies aged 1 to 4 months. [2][3][4][5] The median age of our population was higher because in Italy younger babies are often admitted to NICUs owing to a relatively low number of PICUs. 35 Our population also had more severe parenchymal disease than the classic RSV clinical presentation; the high percentage of bacterial coinfection may explain the more severe hypoxia we found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, acute bronchiolitis leading to PICU admission occurs often in babies aged 1 to 4 months. [2][3][4][5] The median age of our population was higher because in Italy younger babies are often admitted to NICUs owing to a relatively low number of PICUs. 35 Our population also had more severe parenchymal disease than the classic RSV clinical presentation; the high percentage of bacterial coinfection may explain the more severe hypoxia we found.…”
Section: Discussionmentioning
confidence: 99%
“…1 In infants with severe RSV bronchiolitis, CPAP reduces the esophageal pressure time product, and 6 to 7 cm H 2 O CPAP was associated with the greatest muscle unloading, improvement in breathing pattern, and favorable clinical outcome. [2][3][4] In this series, all infants needing NRS were ,1 year old. Younger children cope less well with NRS than older ones, who are more cooperative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During NIV, ten consecutive breaths were analysed every 10 min (after a period of 20 min to allow stabilisation of the breathing pattern) and were used as repeated measures (t1 to t10). At each time interval, RR, dPes and PTPes were calculated from the oesophageal pressure curve for ten consecutive breaths as follows: RR equals 60 divided by the time interval measured between the beginning of two consecutive breaths; dPes is the difference between the oesophageal pressure at the beginning of inspiration and its lowest inspiratory value; PTPes was calculated by multiplying the RR by the area subtended by the inspiratory oesophageal pressure curve without taking into account the thoracic static recoil pressure, as described by others [3,9]. Data were analysed using two-way repeated analysis of variance with Bonferroni correction.…”
Section: Methodsmentioning
confidence: 99%
“…Non-invasive pressure support ventilation (NIV) has been used as a treatment for acute and chronic respiratory failure in children [1][2][3][4]. A recent study showed that NIV is able to unload respiratory muscles safely in children with mean age of 6 years and mean body weight of 22 kg [5].…”
Section: Introductionmentioning
confidence: 99%